ANALYSIS OF THE DIVISION OF JOINT PROPERTY AFTER DIVORCE IN THE PERSPECTIVE OF THE COMPILATION OF THE ISLAMIC LAW IN THE RELIGIUS COURT OF PANGKALAN BALAI (STUDY OF CASE DECISION NO. 458/PDT.G/2020/PA.PKB) - Aprindawati, Amini; Holijah, Holijah; Selma, Muhammad Yahya (JURNAL ILMU SYARIAH, 2023)
This study aims to analyze how the division of joint property after divorce is reviewed in the perspective of the compilation of Islamic law in the Religious Court of Pangkalan Balai. This research is empirical juridical research supported by primary data and secondary data. Through observation and interviews, primary data were obtained from informants, and secondary data were obtained from applicable laws and regulations related to the problem through literature studies, such as books and journals. Theconsequences of this study show that the dispersion of shared resources after separation has been completed with the resources owned by the injured party and the litigants are similarly isolated. This division of property does not violate Islamic law because it is carried out in accordance with existing laws. This division is also done with the evidence presented at the trial, so that the judge can use it to decide how the division of property will be after the divorce. The judge's consideration in judging cases regarding the division of joint property refers to Article 97 of the compilation of Islamic law which explains that widows or widowers divorced life will get one-half of the joint property.